Triangular perspectives of healthcare providers, patients and their families on ICU palliative care: a protocol for a systematic review of qualitative studies - Hui Xu; Lin He; Yuting Shen; Yinghui Zou (BMJ Open)
Introduction In the intensive care unit (ICU), palliative care encounters obstacles such as decision conflicts, psychological stress and cultural differences among patients, families and healthcare providers. The well-being and the care quality of patients are influenced by these factors. The highly technical and curative-focused environment of the ICU presents a challenge for palliative care without appropriate integration. Certainly, it is imperative to comprehend these issues and devise strategies to reconcile curative and palliative needs. This paper employs qualitative metaintegration to appraise the experiences and perspectives of palliative care in the ICU, emphasising its outcomes, barriers and the necessity of balanced care and treatment.Methods and analysis This study conducted a comprehensive search of both the published and unpublished literature (such as grey literature) from a variety of databases, concerning PubMed, Google Scholar, Cochrane Library, CINAHL, Web of Science, Embase, Scopus, PsycINFO, CNKI, Wanfang, CBM and VIP, up to 10 July 2024. The articles will be retrieved and incorporated into EndNote X9 to facilitate organisation. Two independent researchers will evaluate the studies using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Qualitative Research, and a third researcher will resolve all discrepancies. Data extraction and results synthesis will be performed independently based on the JBI qualitative data extraction tool. Finally, the ConQual method will be employed to estimate the calibre of the compiled results.Ethics and dissemination The systematic review was conducted without the necessity of obtaining ethical clearance from a research committee, as it analysed previously published studies that did not contain any personal identifying information of participants. The review’s findings were presented to key stakeholders and submitted for consideration in peer-reviewed journals.PROSPERO registration number CRD42024571594.